Analysis of the Factors Affecting the Open Unemployment Rate in Central Sulawesi Province - Safirda, Safirda; Paembonan, Laendatu (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
Unemployment remains a critical challenge for the Indonesian economy, including in Central Sulawesi Province. Economic growth, measured by Gross Regional Domestic Product (GRDP), and human development quality, measured by the Human Development Index (HDI), are two key factors suspected to influence the Open Unemployment Rate (TPT). This study aims to analyze the influence of GRDP and HDI on the Open Unemployment Rate in Central Sulawesi Province from 2014 to 2023. This study utilised a descriptive quantitative research method using secondary data obtained from the Central Statistics Agency (BPS) for the period 2014–2023. Data collection techniques were carried out through documentation, while data analysis used elasticity analysis to measure the level of responsiveness of TPT changes to variations in GRDP and HDI. Based on the research, the results show that changes in GRDP have a significant and negative effect on the open unemployment rate in Central Sulawesi Province from 2014 to 2023. An increase in GRDP will reduce the open unemployment rate in Central Sulawesi Province. Changes in HDI have a significant and negative effect on the open unemployment rate in Central Sulawesi Province from 2014 to 2023. An increase in HDI will reduce the open unemployment rate in Central Sulawesi Province. The study concludes that both economic expansion and improvements in human capital are effective strategies for reducing unemployment in the region.